Quantitative Imaging of Cerebral Thromboemboli In Vivo The Effects of Tissue-Type Plasminogen Activator - Kim, Dong-Eog; Kim, Jeong-Yeon; Schellingerhout, Dawid; Ryu, Ju Hee; Lee, Su-Kyoung; Jeon, Sangmin; Lee, Ji Sung; Kim, Jiwon; Jang, Hee Jeong; Park, Jung E.; Kim, Eo Jin; Kwon, Ick Chan; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Background and Purpose-Quantitative imaging for the noninvasive assessment of thrombolysis is needed to advance basic and clinical thrombosis-related research and tailor tissue-type plasminogen activator (tPA) treatment for stroke patients. We quantified the evolution of cerebral thromboemboli using fibrin-targeted glycol chitosan-coated gold nanoparticles and microcomputed tomography, with/without tPA therapy. Methods-We injected thrombi into the distal internal carotid artery in mice (n=50). Fifty-five minutes later, we injected fibrin-targeted glycol chitosan-coated gold nanoparticles, and 5 minutes after that, we treated animals with tPA or not (25 mg/kg). We acquired serial microcomputed tomography images for 24 hours posttreatment. Results-Thrombus burden at baseline was 784x10(3)+/- 59x10(3) mu m(2) for the tPA group (n=42) and 655x10(3)x10(3)x10(3) mu m(2) for the saline group (n=8; P=0.37). Thrombus shrinkage began at 0.5 to 1 hour after tPA therapy, with a maximum initial rate of change at 4603 +/- 957 mu m(2)/min. The rate of change lowered to approximate to 61% level of the initial in hours 1 to 2, followed by approximate to 29% and approximate to 1% in hours 2 to 3 and 3 to 24, respectively. Thus, 85% of total thrombolysis over 24 hours (approximate to 500 mu m(2), equivalent to 64% of the baseline thrombus burden) occurred within the first 3 hours of treatment. Thrombus burden at 24 hours could be predicted at around 1.5 to 2 hours. Saline treatment was not associated with significant changes in the thrombus burden. Infarct size was smaller in the tPA group versus saline group (18.1 +/- 2.3 versus 45.8 +/- 3.3 mm(2); P<0.01). Infarct size correlated to final thrombus burden (r=0.71; P<0.01). Time to thrombolysis, completeness of thrombolysis, and tPA therapy were independent predictors of infarct size. Conclusions-Thromboembolic burden and the efficacy of tPA therapy can be assessed serially, noninvasively, and quantitatively using high-resolution microcomputed tomography and a fibrin-binding nanoparticle imaging agent.
Keywords: ACUTE ISCHEMIC-STROKE; CAROTID-ARTERY OCCLUSION; INDIVIDUAL PATIENT DATA; ENDOVASCULAR THERAPY; THROMBUS FORMATION; RANDOMIZED-TRIALS; MOUSE MODEL; HEMORRHAGIC TRANSFORMATION; SYSTEMIC THROMBOLYSIS; COMPUTED-TOMOGRAPHY